2018
DOI: 10.3390/ijerph15102259
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Health in Perinatal and Early Childhood: Awareness, Representation, Knowledge and Practice of Southern France Perinatal Health Professionals

Abstract: The exposure of adults of reproductive age as well as pregnant women and children to environmental contaminants is of particular concern, as it can impact fertility, in utero development, pregnancy outcomes and child health. Consequently, the World Health Organisation (WHO) and international societies advocate including Environmental Health (EH) in perinatal care, yet perinatal health professionals (HPs) hardly put these recommendations into practice. In 2017, a cross-sectional study was performed in a large p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 28 publications
3
19
0
8
Order By: Relevance
“…An American survey found that less than 20% of obstetricians routinely interview their patients about their environment [32]. The difficulties most frequently cited were the lack of training and knowledge in environmental health, the lack of evidence-based information, the short duration of consultations [30,31,32,33], the fear of patient reactions, and the lack of solutions [33].…”
Section: Discussionmentioning
confidence: 99%
“…An American survey found that less than 20% of obstetricians routinely interview their patients about their environment [32]. The difficulties most frequently cited were the lack of training and knowledge in environmental health, the lack of evidence-based information, the short duration of consultations [30,31,32,33], the fear of patient reactions, and the lack of solutions [33].…”
Section: Discussionmentioning
confidence: 99%
“…In an American study, only 1 out of 15 obstetricians said he had been trained in environmental health, a field in which the participants were nonetheless interested, and would like to be trained [17]. In France, only 17% of the health professional population had heard about environmental health during the course of their initial training [13].…”
Section: Discussionmentioning
confidence: 99%
“…To date, among the studies on the knowledge, attitudes, beliefs, and practices of prenatal professionals in the field of environmental health [6], only 7 out of 43 are European. Three recent studies took place in France [11,12,13] but did not focus on vulnerable populations. We conducted a qualitative study whose objective was to identify the knowledge, attitudes, and practices on environmental health of French prenatal professionals working with an underprivileged population.…”
Section: Introductionmentioning
confidence: 99%
“…Sunyach et al. (2018) conducted a survey on perinatal health professionals (HPs) in southeastern France. According to this survey, perinatal HPs lack training and understanding of the reproductive risks about daily environmental exposure.…”
Section: Introductionmentioning
confidence: 99%